2022
DOI: 10.1093/braincomms/fcac183
|View full text |Cite
|
Sign up to set email alerts
|

Interictal epileptiform discharges show distinct spatiotemporal and morphological patterns across wake and sleep

Abstract: Presurgical evaluation of mesial temporal and neocortical focal pharmacoresistant epilepsy patients using intracranial EEG recordings has led to the generation of extensive data on interictal epileptiform discharges, located within or remotely from seizure onset zones. In this study, we used this data to investigate how interictal epileptiform discharges are modulated and how their spatial distribution changes during wake and sleep and analysed the relationship between these discharge events and seizure onset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 42 publications
0
16
2
Order By: Relevance
“…Although this regional effect was shown in NREM sleep, 13,14 previous studies did not find an effect of brain areas on IED rates in REM sleep and wakefulness. 14 Relative to wakefulness, neocortical regions showed a suppression of IEDs by REM sleep, whereas mesiotemporal regions showed an increase in IEDs. This effect was observed in both SOZ and non-SOZ regions and may be due to major cholinergic innervations to neocortical regions, mediating neuronal desynchronization, resulting in more suppression of epileptic activity in the neocortex.…”
Section: Ied Suppression By Rem Sleepmentioning
confidence: 56%
See 2 more Smart Citations
“…Although this regional effect was shown in NREM sleep, 13,14 previous studies did not find an effect of brain areas on IED rates in REM sleep and wakefulness. 14 Relative to wakefulness, neocortical regions showed a suppression of IEDs by REM sleep, whereas mesiotemporal regions showed an increase in IEDs. This effect was observed in both SOZ and non-SOZ regions and may be due to major cholinergic innervations to neocortical regions, mediating neuronal desynchronization, resulting in more suppression of epileptic activity in the neocortex.…”
Section: Ied Suppression By Rem Sleepmentioning
confidence: 56%
“…Emerging evidence suggests that the spatial distribution of IEDs during sleep may extend beyond the EZ 13,14 . Specifically, mesiotemporal regions show higher IED rates during NREM sleep, regardless of whether they contain the SOZ 13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using invasive EEG, Penfield and Jasper (1954) later reported an increase of IEDs when certain patients became drowsy or fell asleep. Since then, IEDs have been consistently found to occur more often during sleep (Lieb et al, 1980; Ferrillo et al, 2000; Bagshaw et al, 2009; Goncharova et al, 2009; Karoly et al, 2016; Rossi et al, 1984; Sammaritano et al, 1991; Spencer et al, 2016; Lambert et al, 2018; Fouad et al, 2022). Indeed, long-term recordings have found robust 24 hour periods, peaking between midnight and 5pm (Anderson et al, 2015; Spencer et al, 2016; Baud et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Del Felice et al (2015) reported a statistical increase in the amplitude of cortical and mesial temporal spikes during N2 versus wakefulness, but these findings were based on a very limited number of observations (an average of 39 spikes in N2, 21 spikes during wakefulness, none during SWS or REM). Recently, Fouad et al (2022) investigated differences in spike morphology using a feature extraction method (Liu et al, 2013), reporting amplitude differences between brain regions and SOZ, but no statistically significant differences between sleep stages. A non-significant trend towards increased amplitudes in deeper stages of sleep could be observed, but only within median brain regions, and only from the SOZ.…”
Section: Introductionmentioning
confidence: 99%